THE DISPUTE OF AMBALAT IN THE PERSPECTIVE OF INDONESIAN FOREIGN POLICY IN THE POST-NEW ORDER ERA - Hadi, Syamsul (Indonesian Journal of International Law, 2014)
This article analyzes the Ambalat territorial dispute between Indonesia and Malaysia, viewing from the perspective of Indonesian foreign policy in the Post-New Order era. The writer argues that Ambalat is a typical case in which Indonesian foreign policy had been widely influenced by public pressures which force government to take a firm stance against Malaysia. The practices of democratic system, including free media, have become an important factor behind such firm stance, along with the growing nationalism amongst public in the Post-New Order Indonesia. However, in relations with the willingness to maintain a regional influence in ASEAN, the government actually does not really intent to involve in an open war.